Perubahan Sosial Ekonomi Masyarakat di Kelurahan Oesapa dan Sekitarnya Akibat Hadirnya Pemondokan di Kawasan Pemukiman - Rudi Rohi; Lasarus Jehamat (Badan Penelitian dan Pengembangan Daerah Kota Kupang, 2017)
This article focuses on the changing of sosio-economic in Oesapa and surroundings due to the presence of the lodgings at residential areas. By using mixed methods based on survey and depth interview, this study gaineda number of interesting findings.Social reality in the areaswhere this research was conducted shows low social cohesion, social structure and function is transformed into economy, and the changing of sub system relationship. The changing driven by various factors including population, education, and economic growth - internal, and determination of information technology and acculturation - external. These thingshave impact on widespread of social relation and networks, economic growth, socialization of cultural diversity - positive, and any number of social problems with str uctural and cultural faces - negative.